2019
DOI: 10.18553/jmcp.2019.25.11.1236
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Socioeconomic Disparities in Use of Direct-Acting Antivirals Among Medicare Beneficiaries with Chronic Hepatitis C, 2014-2016

Abstract: BACKGROUND: New hepatitis C virus (HCV) drugs – direct acting antivirals (DAAs) – are highly effective but costly. This raises a concern about limited access to DAAs by vulnerable populations. Prior studies of disparities in DAA use across patient groups showed mixed results, but their generalizability was limited due to using data from a commercial insurer(s) or from 2014 only – the first year of DAAs. Disparities in DAA use in a national cohort in the years when more DAAs were available is unknown. OBJECTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…The situation is less clear with our Medicare respondents, although there have been reports of difficulties with receipt of DAAs among Medicare recipients, particularly those lacking Part D coverage or with Part D coverage subject to high copays, or with Medicare/Medicaid dual coverage subject to state‐specific Medicaid drug coverage rules. ( 48 ) Unfortunately, not all our study sites (each in a different state) collected information on Part D coverage, so we were not able to discern whether or to what degree this might be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is less clear with our Medicare respondents, although there have been reports of difficulties with receipt of DAAs among Medicare recipients, particularly those lacking Part D coverage or with Part D coverage subject to high copays, or with Medicare/Medicaid dual coverage subject to state‐specific Medicaid drug coverage rules. ( 48 ) Unfortunately, not all our study sites (each in a different state) collected information on Part D coverage, so we were not able to discern whether or to what degree this might be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies of Medicare populations with HCV infection. 8,12,30 A major reason for low DAA uptake is the insufficient numbers of physicians with experience in cases of HCV infection, especially in rural and underserved areas. 12 However, with task-shifting treatment models such as…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] For example, Jung et al evaluated 281,810 Medicare patients with chronic HCV and observed significantly higher odds of HCV therapy in African Americans compared to non-Hispanic whites (adjusted OR 1.24, 95% CI 1.22-1.27), but no significant differences in Hispanics. [15] However, Spradling et al evaluated the Chronic Hepatitis Cohort Study from 2014-2015 and observed 30% lower odds of treatment in African Americans compared to non-Hispanic whites; Wong et al evaluated 29,544 chronic HCV patients across four community-based healthcare systems and observed significantly lower odds of HCV treatment in Hispanics compared to non-Hispanic whites (adjusted odds ratio 0.48, 95% CI 0.39-0.60). [8,14] We aim to evaluate the overall rates of HCV linkage to care (LTC), retention to care, and access to treatment in an ethnically diverse safety-net population with a specific focus on sex-specific and race/ ethnicity-specific disparities.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2020 / mentioning
confidence: 99%
“…Existing studies have reported on race/ethnicity-specific disparities in access to HCV treatment. [ 13 , 14 , 15 ] For example, Jung et al . evaluated 281,810 Medicare patients with chronic HCV and observed significantly higher odds of HCV therapy in African Americans compared to non-Hispanic whites (adjusted OR 1.24, 95% CI 1.22–1.27), but no significant differences in Hispanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation